Ropivacaine Inhibits Lung Cancer Cell Malignancy Through Downregulation of Cellular Signaling Including HIF-1α In Vitro - Shen, Junmei; Han, Lina; Xue, Yongxian; Li, Chao; Jia, Huiqun; Zhu, Kangsheng (Frontiers in Pharmacology, 2022)
Abstract Background: Ropivacaine is widely used to induce regional anesthesia during lung cancer surgery. Previous studies reported that amide-linked local anesthetics, e.g., ropivacaine, affected the biological behavior of lung adenocarcinoma cells but the conclusion is controversial and warrants further study. This study set out to investigate the biological effects of ropivacaine on cultured lung cancer cells and underlying mechanisms. Methods: Lung cancer cell lines (A549 and H1299) were cultured and then treated with or without ropivacaine (0.5, 1 and 2 mM) for 48 or 72 hrs. Their proliferation, migration and invasion together with cell death and molecules including HIF-1α, VEGF, MMP-1, MMP-2 and MMP-9 expression associated with these changes were determined. Results: Ropivacaine significantly inhibited proliferation and migration, invasion and cell death in a concentration dependent manner in both cell lines. Ropivacaine also promoted cell death and induced a concentration- and time- dependent cell arrest towards the G0/G1 phase. VEGF, MMP-1, MMP-2, MMP-9 and HIF-1α expression in both cell lines were also inhibited by ropivacaine in a concentration related manner. Conclusion: Our data indicated that ropivacaine inhibited lung cancer cell malignancy which may be associated with down-regulations of cell survival associated cellular molecules. The translational value of the current work is subjected to further study.